Решить уравнение  3(x+1)(x+2) - ( 3x - 4)(x+2) = 36                                                                                                                        x+(x-5) =  11                                           ...

Решить уравнение   3(x+1)(x+2) - ( 3x - 4)(x+2) = 36                                                                                                                          x+(x-5) =  11                                                                             ----- -------------                                                                                                                                2               
Гость
Ответ(ы) на вопрос:
Гость
3*x2+3-3x2+6-4x+8=36 3x2+9-3x2+6-4x+8=36 20-4x=36 -4x=36-20 -4x=6 x=6:(4) x=-1,5
Не нашли ответ?
Ответить на вопрос
Похожие вопросы